Do Eastern European immigrants assimilate faster in terms of wages than Latin American immigrants in the U.S.? - Ganish, Anna; Slaný, Martin, 1982-; Klement, Josef, 1990-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2026)
This thesis examines wage assimilation among Latin American and Eastern European immigrants in the United States using IPUMS ACS microdata and pooled OLS regression models. The analysis reveals that both groups experience rising wages with years since migration, but their assimilation patterns differ: Latin Americans show faster initial wage growth, while Eastern Europeans display slower but more sustained long-term gains. The results show that both groups experience clear wage assimilation, with wages rising as time in the U.S. increases. Latin Americans assimilate faster initially (≈2.9% wage growth per year), but their growth slows more sharply over time. Eastern Europeans assimilate more slowly (≈2.5% per year) but sustain wage growth longer due to a flatter quadratic effect.
Vedoucí práce: Martin Slaný
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses